Highly chemoselective NH- and O-transfer to thiols using hypervalent iodine reagents: synthesis of sulfonimidates and sulfonamides - Tota,A; St,John-Campbell S; Briggs,E; Ogalla,Estévez G; Afonso,M; Degennaro,L; Luisi,R; Bull,JA (Organic Letters, 2018)
Aryl thiols can be selectively converted to sulfonimidates or sulfonamides with 3 new S–X connections being made selectively in one-pot. Using hypervalent iodine reagents in the presence of ammonium carbamate, NH- and O-groups are transferred under mild and practical conditions. Reducing the loading of ammonium carbamate changed the product distribution, converting the sulfonimidate to the sulfonamide. Studies into the possible intermediate species are presented, suggesting that multiple pathways may be possible via sulfinate esters, or related intermediates, with each species forming the same products.